Pregnancy in Practice : Expectation and Experience in the Contemporary US - Sallie Han (Berghahn Books, 2013)
This book is an anthropological study of â€œordinaryâ€ pregnancy. It describes and discusses pregnancies that are more or less normal, healthy, and uncomplicated. They are the kind of pregnancies that most women in the United States have, notwithstanding portrayals in the popular media of medical emergencies and reproductive dramas. The focus of this book is on the practices of ordinary pregnancy, which especially emphasize literacy and consumption. In this book, I consider the importance and meaning of everyday experiences such as reading pregnancy advice books, showing ultrasound â€œbaby picturesâ€ to friends and co-workers, and decorating the nursery in anticipation of the new arrival.